(untitled) (Revista de História da UEG (REVHIST), 2020)
This article analyze the installation of the multipurpose gymnasium in the city of Alfenas and examine some aspects of teaching practices established during the first decade of its existence. With a look at the school culture, the documents located at the school and two interviews were taken as sources, which allowed examining the specifics of practices that were established in the institution in a period of significant changes in Brazilian education after the implementation of law no. 5,692/71. The research showed the movement of structuring the school, its vocational characteristic and the functioning of technical disciplines. Daily experiences indicated the construction of civic rituals that fostered a collective identity constitution, but also showed the conflicts and resistance of teachers and students. Keywords: School culture. Multipurpose. Alfenas.